C22 disrupts embryogenesis and extends C. elegans lifespan - Beydoun, Safa; Sridhar, Aditya; Tuckowski, Angela M.; Wang, Emily; Leiser, Scott F. (Frontiers in Physiology, 2023)
Caenorhabditis elegans is an instrumental model in aging research due to its large brood size, short lifespan, and malleable genetics. However, maintaining a synchronous nematode population for longevity studies is challenging and time consuming due to their quick rate of development and reproduction. Multiple methods are employed in the field, ranging from worm strains with temperature dependent sterility to DNA replication inhibitors such as 5'-fluorodeoxyuridine (FUdR). In this study, we characterize a small molecule (C22) that impairs eggshell integrity and disrupts early embryogenesis to determine its applicability as a potential FUdR alternative. We find that C22 prevents egg hatching in a concentration dependent manner. However, it extends the lifespan of wild type worms and can induce FMO-2, a longevity regulating enzyme downstream of dietary restriction. Our results suggest that C22 is unlikely to be widely useful as an alternative to FUdR but its mechanism for lifespan extension may be worth further investigation.